Economic analysis of ecosystem based adaptation and engineering options: A case study from Udayapur, Nepal (Nepal Journal of Environmental Science, 2015)
Ecosystem services are vital to our well-being as they directly or indirectly support our survival and quality of life. But, the growing impact of climate change diminishes the benefit from ecosystem services. Therefore, identifying possible applicable adaptation options are inevitable to reduce the effect of climate change. The present research is based on a case study of Ksedi River watershed, Ajgada Village in Udaypur district of Nepal. The study demonstrates the comparison between different options to deal with flood and make a sound decision, based on economic rationale for long-term benefits. The present study compares ecosystem based adaptation options with engineering options using cost benefit analysis in order to protect village from flooding. Through stakeholder and expert consultations, ecosystem based adaptation options and economic options that are feasible in the village and catchment to mitigate the floods were listed. Economic analysis of these options and the different combinations were done using cost benefit analysis. Analysis was carried out for each of the different combination of options. Focus on ecosystem based adaptation options provide high benefit to cost return in terms of avoided damages and considering engineering options efficient in flood and erosion control in initial stage in spite of its high cost. The study suggests that reforestation in upland forest areas; plantation along riverbed and management of rangeland should be prioritized. Similarly, preparation of flood model, flood height damage curve and flood vulnerable maps specific to the site will help decision makers to implement site specific adaptation options.